(untitled) (Research, Society and Development, 2022)
Objective: To analyze the factors related to the high incidence of gestational and congenital syphilis in Brazil. Methodology: An integrative review of studies published between 2016 and 2021 was conducted through the LILACS, MEDLINE, PubMed and SciELO databases. Results: The main factors related to the high incidence of gestational and congenital syphilis, failure in diagnostic methods, underreporting, non-adherence to preventive and control methods, as well as the non- association of concomitant treatment of pregnant women and their partners were identified. In addition, there is a shortage of the raw material of benzathine penicillin, a first-line drug for treatment, and a deficiency in the qualification of health professionals who work in the face of treponemal infection in pregnant women and newborns. Conclusion: Treatment failure and increased incidence of gestational and congenital syphilis is directly related to the lack of training of health professionals, the non-treatment of the partner and the late start of prenatal care.